KARAKTERISTIK BERPIKIR KREATIF SISWA KELAS VII SMP N 1 KRAGAN DALAM MEMECAHKAN DAN MENGAJUKAN MASALAH MATEMATIKA MATERI PERBANDINGAN DITINJAU DARI GAYA KOGNITIF - Argarini, Dian Fitri; Budiyono, Budiyono; Sujadi, Imam (Journal of Mathematics and Mathematics Education, 2014)
Abstract: The research objectives were to determine and to describe creative thinking characteristic of 7th grade students of SMP N 1 Kragan in solving and proposing problem at comparative case seen from the cognitive style. This research belonged to descriptive research by qualitative-explorative approach. The sample was taken by purposive sampling technique. The subjects being used in this research were 4, those were 2 students with field dependent cognitive style and 2 students with field independent cognitive style. The subject grouping based on cognitive style was taken by group embedded figures test. There were two instruments that were used to collect the data of this research. The first instrument was solving and proposing problem test instrument. The second was interview guidance. They were validated by using the time triangulation test and the reference fulfillment. The data were analyzed using a Miles and Hubermanâs concept, that was data reduction, presentation, and conclusion.. The results of this research show as follows, (1) Creative thinking characteristics of students who had field dependent cognitive style in solving and proposing problem were as follows. The fluency aspect was shown by the students through 4 stages of creative thinking process, both in solving and proposing the problem. The four stages were preparation stage, incubation stage, illumination stage, and verification stage. The flexibility aspect in solving problems appeared when the students gave the other alternative answer, whereas this aspect was not fulfilled in proposing the problems.Â  The originality aspect was not fulfilled in solving and proposing problems. (2) Creative thinking characteristics of students who had field independent cognitive style in solving and proposing problem were as follows. The fluency aspect was shown by the students through 4 stages of creative thinking process, both in solving and proposing the problem. The four stages were preparation stage, incubation stage, illumination stage, and verification stage. The flexibility aspect in solving problems was shown when the students gave the other alternative answer, while in proposing the problem this aspect was not completed because students were able to make only one question. The originality aspect in solving the problem could be seen when the students gave a new way solution and thisÂ  was different from the previous one. Meanwhile in proposing the problems, aspet of originality was not fulfilled.Keywords:Â Â  creative thinking characteristics, solvingÂ  problems, proposing problems, cognitive style